The Microglial α7-Acetylcholine Nicotinic Receptor Is a Key Element in Promoting Neuroprotection by Inducing Heme Oxygenase-1viaNuclear Factor Erythroid-2-Related Factor 2 - Parada, Esther (2017)
The deposited article is a post-print version.